Failure mechanisms of carbonate rock landslides: structure, karst generation and reservoir water fluctuations - Chen, Taiyi; Sanjou, Michio; Hiraishi, Tetsuya; Xu, Guangli (Geomorphology (Amsterdam, Netherlands), 2025)
Carbonate rock landslides are a worldwide phenomenon often accompanied by faults and karstification. However, the formation mechanism and research method for this type of landslide have not been extensively investigated. The Baihetan hydropower station is located in China. It is the second largest hydropower station and its water level fluctuation range is the largest in the world. The Gengdi landslide in the Baihetan Reservoir area that began impounding in April 2021 is selected as the research subject. The inherent structural features and karstification in this region control the slope stability and failure behavior from the micro- to macro-scale. The regularity and systematization of the idealized Riedel shear model, fault zone model, and karstification model of the landslide are observed through regional structure, field outcrop, in-situ test, and laboratory test. The findings indicated that failure mechanisms are associated with the strike-slip fault and carbonate rock deterioration. The evolution process is compared using numerical simulation results and on-site monitoring data, emphasizing the effect of the structural geological environment and reservoir water fluctuations on the landslide. The fault gouge and carbonaceous slates are rich in ferrous sulfide and iron dissolution in basalt, which aggravates the deterioration of carbonate rocks. A physical and karstification model of the reaction zone is established, and the mechanism of dissolution and seepage effect on fault zone deformation is analyzed quantitatively. Fault zone, palaeokarst and reservoir water fluctuations jointly promote the formation of carbonate rock mass landslides. The findings provide a deeper insight into identifying and understanding the mechanical properties of reservoir carbonate rock landslides under the influence of strike-slip faults. •The spatial model of faults and palaeokarst control the failure mechanisms.•The disaster-inducing effects of dissolution and seepage are presented.•A model of faults-dissolution-reservoir water for landslides has been proposed.